Pelestarian Nilai-Nilai Sumang Pada Kearifan Lokal Didong Sebagai Perwujudan Masyarakat Yang Berkarakter - Saputra, Edy; Zulmaulida, Rahmy (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2023)
Local wisdom in Gayo society has been passed down from generation to generation, two of which are Sumang and Didong. Sumang is a cultural system that has roots in the Gayo people as an archetype and foundation of life. Meanwhile, Didong is a local art from the Gayo area that combines vocal, dance and literature. This research uses a type of qualitative research with a descriptive approach, which aims to preserve and restore the implementation of Sumang and Didong, as well as to describe the acceptance of the Gayo Highlands community towards the idea of ​​implementing Sumang values ​​into Didong art in order to achieve a society with character. All formal and non-formal art galleries and the Ceh Didong in the Gayo Highlands became the population in this study, with the sample being the Renggali Studio and 3 Cehs. Data collection techniques using observation and interviews. Research data were analyzed using descriptive data analysis techniques from observations and interviews. The results of the study show that: (1) the people of Gayo Highlands agree with the idea of ​​applying Sumang values ​​to Didong art, and (2) the role of the younger generation through actual practice of applying Sumang values ​​in their activities and exemplifying the application of Sumang values ​​to in Didong art without changing the characteristics of Didong art.